Economic analysis of surface and sub-surface drip fertigated maize (Zea mays)–wheat (Triticum aestivum) system under different nutrient management practices and irrigation schedules - SAIRAM, ARPULA; LAL, KHAJANCHI; SUDISHRI, SUSAMA; KHANNA, MANOJ; BRAHMANAND, P S; SHIVAY, YASHBIR SINGH; ABRAHAM, GERARD; MEENA, VED PRAKASH (The Indian Journal of Agricultural Sciences, 2026)
The study was carried out during two consecutive years (2022–23 and 2023–24) in both rainy (kharif) and winter (rabi) seasons at Indian Agricultural Research Institute, New Delhi to analyse the financial viability of various nutrient management options i.e. chemical, organic, integrated, and natural farming in maize (Zea mays L.)–wheat (Triticum aestivum L.) cropping system irrigated at 0.8 and 1.0 crop evapotranspiration (ETc) for surface drip (SDI) and sub-surface drip irrigation (SSDI). The effects were also compared with the farmers’ conventional practice of surface irrigation and soil application of 100% of the recommended nitrogen, phosphorus, and potassium fertiliser doses. The system maize equivalent yield (SMEY) obtained with the integrated nutrient management (50% RDN through FYM + vermicompost and 50% RDN through chemical fertilisers) was found to be the higher and at par with that of the chemical nutrient management (10.6 Mg/ha) and conventional system (10.3 Mg/ha) but 14% and 24% higher compared to organic and natural farming nutrient management options, respectively. SMEY productivity was found equal in SDI and SSDI but improved significantly at irrigation schedule of 1.0 ETc compared to 0.8 ETc. At the system level, integrated nutrient management under drip irrigation used substantially less water (2270–2973 m³/ha) than surface irrigation (100% RDF) (4650 m³/ha), while simultaneously achieving higher system water use efficiency (3.61–4.78 kg/m3) compared with surface irrigation (2.23 kg/m3). The soil properties (available K, microbial carbon and dehydrogenase activity) were found significant in organic and chemical methods. Due to less input cost, the cost of cultivation in natural farming was 12, 20 and 17% lower than that in chemical, organic and integrated nutrient management options, respectively. Pooled analysis showed that integrated nutrient management recorded the highest gross returns, net income, and benefit-cost ratio in the maize–wheat system, with SSDI at 1.0 ETc plus integrated nutrients producing 17% higher net income than conventional surface irrigation with soil-applied NPK.